PROSES PEMBUATAN MINYAK PELUMAS MINERAL DARI MINYAK BUMI - Pratama, Alfiansyah Aji (Jurnal Kompetensi Teknik, 2019)
base mineral oil was one of many product of crude oil fraction which pass through many refining process in refinery. In order to obtain fraction of lubricant oil (base mineral oil) from crude oil need much kind of process to get important traits from lubricant oil. Wherefore the crude oil contain many hydrocarbon compounds and very complex. To get high quality lubricant oil need many processing units and mutually integrated so in the lubricant oil did not contain bad compound later on used in the mechanical engine or vehicle.